Conceptions of mobile emergency service health professionals concerning psychiatric emergency - Diego Bonfada; Jacileide Guimarães; Andiara Araújo Cunegundes de Brito (Universidade Federal do Ceará, 2012)
Under the Brazilian Psychiatric Reformation, assistance to psychological seizures represents a challenge for the emergency services. Therefore, the objective of this paper is the analysis of the conceptions of health professionals who work at the Mobile Emergency Service in Natal on psychiatric emergency care. This paper is, then, a qualitative study that used interviews as tools for collecting information. By using thematic analysis, the speeches were grouped into three categories: the stigma on patients and the professionals' fear of services interventions in psychiatric emergencies; having psychiatric emergencies regarded as harmful to patients and others' security; psychiatric emergencies being taken as patients' aggressiveness or severe depression. The data collected indicate that the interviewed professionals' ideas are supported by elements associated with the ideology that insanity implies social segregation and dangerousness. Thus, the survey prompted reflection on relevant issues to the process of psychiatric reformation implementation.